Ethylene response factor MdERF4 and histone deacetylase MdHDA19 suppress apple fruit ripening through histone deacetylation of ripening-related genes. Issue 4 (28th January 2022) - Hu, Yanan; Han, Zhenyun; Wang, Ting; Li, Hua; Li, Qiqi; Wang, Shuai; Tian, Ji; Wang, Yi; Zhang, Xinzhong; Xu, Xuefeng; Han, Zhenhai; Lü, Peitao; et al.
Abstract: Histone deacetylase enzymes participate in the regulation of many aspects of plant development. However, the genome-level targets of histone deacetylation during apple ( Malus domestica ) fruit development have not been resolved in detail, and the mechanisms of regulation of such a process are unknown. We previously showed that the complex of ethylene response factor 4 (MdERF4) and the TOPLESS co-repressor (MdTPL4; MdERF4–MdTPL4) is constitutively active during apple fruit development (Hu et al., 2020 ), but whether this transcriptional repression complex is coupled to chromatin modification is unknown. Here, we show that a histone deacetylase (MdHDA19) is recruited to the MdERF4–MdTPL4 complex, thereby impacting fruit ethylene biosynthesis. Transient suppression of MdHDA19 expression promoted fruit ripening and ethylene production. To identify potential downstream target genes regulated by MdHDA19, we conducted chromatin immunoprecipitation (ChIP) sequencing of H3K9 and ChIP-quantitative polymerase chain reaction assays. We found that MdHDA19 affects ethylene production by facilitating H3K9 deacetylation and forms a complex with MdERF4–MdTPL4 to directly repress MdACS3a expression by decreasing the degree of acetylation. We demonstrate that an early-maturing-specific acetylation H3K9ac peak in MdACS3a and expression of MdACS3a were specifically up-regulated in fruit of an early-maturing, but not a late-maturing, cultivar. We provide evidence that a C-to-G mutation in the ethylene-responsive element binding factor-associated amphiphilic repression motif of MdERF4 reduces the repression of MdACS3a by the MdERF4–MdTPL4–MdHDA19 complex. Taken together, our results reveal that the MdERF4–MdTPL–MdHDA19 repressor complex participates in the epigenetic regulation of apple fruit ripening. Abstract : One-sentence summary: Global changes in histone modifications that occur during apple fruit ripening.